(untitled) (Jurnal Wahana Konseling, 2024)
This study aims to describe nomophobic behavior before and after being given group guidance services using the role playing method and test the effectiveness of group guidance using the role playing method to minimize students’ nomophobic tendencies. ​This type of research is quantitative with experimental method. The research population is phase F students of SMA N 1 Gunung Talang totaling 20 people, the sample amounted to 10 people with purposive sampling technique. The instrument used is a questionnaire, while for data analysis with percentage techniques and t tests. The results of this study indicate that 1) The description of students’ nomophobia behavior before being given group guidance services using the role playing method is in a fairly high category. 2) The description of students’ nomophobic behavior after being given group guidance services using the role playing method is in the low category. 3) Group guidance using the role playing method to minimize the tendency of nomophobia of students is effective before and after being given the service. Penelitian ini bertujuan untuk mendeskripsikan perilaku nomophobia sebelum dan sesudah diberikan layanan bimbingan kelompok dengan menggunakan metode role playing dan menguji efektifitas bimbingan kelompok dengan menggunakan metode role playing untuk meminimalisir kecenderungan nomophobia peserta didik. Jenis penelitian kuantitatif dengan metode eksperimen. Populasi peneltian adalah peserta didik fase F SMA N 1 Gunung Talang yang berjumlah 20 orang, sampel berjumlah 10 orang dengan teknik purposive sampling. Instrument yang digunakan adalah angket, sedangkan untuk analisis data dengan teknik persentase dan uji t. Hasil penelitian ini menunjukkan bahwa 1) Gambaran perilaku nomophobia peserta didik sebelum diberikan layanan bimbingan kelompok dengan menggunakan metode role playing berada pada kategori cukup tinggi. 2) Gambaran perilaku nomophobia peserta didik setelah diberikan layanan bimbingan kelompok dengan menggunakan metode role playing berada pada kategori rendah. 3) bimbingan kelompok dengan menggunakan metode role playing untuk meminimalisir kecenderungan nomophobia peserta didik efektif sebelumdan sesudah diberikan layanan.